Study The Influence of Forming Conditions Like Deformation Speed on Void Closure in Open Die Forging - Ali, Alaa Hassan (Al-Khwarizmi Engineering Journal, 2019)
This paper presents an investigation to the effect of the forming speed on healing voids that inhabit at various size in an ingot. The study was performed by using finite element method with bilinear isotropic material option, circular type voids were considered. The closure index was able to predict the minimum press force necessary to consolidate voids and the reduction. The simulation was carried out, on circular cross-section lead specials containing a central void of different size. At a time with a flat die, different ratio of inside to outside radius was taken with different speed to find the best result of void closure.